Pendampingan Perancangan Modul Tentang pembelajaran PAI - Yastrid; Nurwahidah; Sudirman P; Syarifuddin; Sartina (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2022)
PAI learning at SDN 250 Ujunge about the limited teaching materials. This study aims to develop students’ interest in learning pie about memorizing short letters and the mearning of the verse. This reseaarch is a develeopment research with a learning moodel of memorizing, listening and understanding. The results of designing the pie learning module are known that the pie medule is feasible to be taught and the feasiofbility of teaching materials is very good from the aspect of the quality of the material and aspects of the benefits of the material. Thus, bassed on the results of the assessment obtained, it can be coucludedthaat the module on learning pai is very feasible to use.